'Push or pull'? Framing immigration in times of crisis in the European Union and the United States. Issue 5 (3rd July 2020) - Hadj Abdou, Leila
ABSTRACT: Migration has become a highly divisive, polarizing issue. This article contributes to the understanding of this polarization by looking at interpretations of migration during critical junctures. It explores discursive framings during the recent migration crises in the European Union and the United States. Analysing interview data collected between 2014 and 2018 with over 100 governance actors, it finds that similar interpretations emerge among the same type of actors' groups across both settings. This finding emphasizes the role of situated agency for framing processes. Frames in both cases establish a perspective of migration as a tragedy, and focus, depending on the type of governance actor, either on pull factors in countries of arrival or push factors in countries of origin as the main cause of immigration, leading to conflicting ideas as to how to respond to the crisis. These conflicting understandings, the article concludes, further fuel the existing socio-political divides.